Stimulation Model Growth And Language Development Of Children Autism In Health Promotion - Atik Badi'ah; Ravik Karsidi; Ahmad Arman Subijanto; Diffah Hanim (Humanistic Network for Science and Technology (HNST), 2018)
Background: Autism is a developmental disorder caused organic brain damage, difficulty communicating verbal, nonverbal. Need supervision and parental attention. The stimulation helps stimulate the brain to produce hormones in its development. Purpose: (1) analyze the internal factors, external influence growth and language development of children with autism (2) analyze the relationship between nutritional status and the growth and language development of children with autism (3) analyze the effect of stimulation of the growth and development of the language development of children with autism (4) formulate a model of growth stimulation and language development of autistic children in health promotion. Method: This type of research was a research and development (R&D), with quasi experimental method, time series design. The study was conducted in 7 autism school in Yogyakarta. The total sample of 90 children with autism. Conducted in November 2015 and April 2016. Data were analyzed using multiple linear regression and Ods Ratio, Mann Whitney and Wilcoxon. Results: (1) internal factors (postnatal) and external (race) affecting growth and language development of children with autism, (2) there was a relationship with the nutritional status of growth and language development of children with autism p